TREN PENGETAHUAN SIKAP DAN PERILAKU (PSP) REMAJA TERHADAP ISU KEPENDUDUKAN - Titisari, Anastasia Septya (PIRAMIDA, 2018)
Adolescents are group of population that contributte in demographic bonus. This occurs when the number of productive ages is greater than the nonproductive. If not managed properly, demographic bonuses will result in negative effects to development. Therefore, adolescents should be equipped with useful sciences. One of them is concerning population. Besides providing an understanding of population control, the goal is also to provide an understanding the maturing age of marriage. This is related to fulfilling the rights of health and reproduction for adolescents. This study discusses about knowledge, attitude, and behaviour trend of adolescents (15-24 years old) towards population seen from RPJMN Survey data (2007-2015). The result shows that adolescent knowledge about fertile period and pregnancy is still fluctuating. As for methods of contraceptive knowledge and the willingness to use contraceptive in the future having an increasing trend. The RPJMN survey shows most adolescents know proper age of marriage and having children. The survey data trend also shows that adolescent attitudes tends to mature the age of marriage, to plan the number of children, and to control the birth space. There is also an increase in the percentage of adolescents who become increasingly concerned about population issues by knowing the effects of population growth and realizing the importance of government programs in regulating population growth..